Development of self-compatible Chinese cabbage lines of Chiifu through marker-assisted selection - Chang, Lichun; Liang, Jianli; Cai, Xu; Zhang, Li; Li, Yufang; Wu, Jian; Wang, Xiaowu (Frontiers in Plant Science, 2024)
The continuously refined genome assembly of the Chinese cabbage accession Chiifu is widely recognized as the reference for Brassica rapa. However, the high self-incompatibility of Chiifu limits its broader utilization. In this study, we report the development of self-compatible Chiifu lines through a meticulous marker-assisted selection (MAS) strategy, involving the substitution of the Chiifu allele of MLPK (M-locus protein kinase) with that from the self-compatible Yellow Sarson (YS). A YSbased marker (SC-MLPK) was employed to screen 841 B. rapa accessions, confirming that all eight accessions with the mlpk/mlpk (mm) genotype exhibited self-compatibility. Additionally, we designed 131 High-Resolution Melting (HRM) markers evenly distributed across the B. rapa genome as genomic background selection (GBS) markers to facilitate the introgression of self-compatibility from YS into Chiifu along with SC-MLPK. Genome background screening revealed that the BC3S1 population had a proportion of the recurrent parent genome (PR) ranging from 93.9% to 98.5%. From this population, we identified self-compatible individuals exhibiting a high number of pollen tubes penetrating stigmas (NPT) (>25) and a maximum compatibility index (CI) value of 7.5. Furthermore, we selected two individuals demonstrating significant similarity to Chiifu in both genetic background and morphological appearance, alongside self-compatibility. These selected individuals were selfpollinated to generate two novel lines designated as SC-Chiifu Lines. The development of these selfcompatible Chiifu lines, together with the SC-MLPK marker and the set of HRM markers, represents valuable tools for B. rapa genetics and breeding.